2002
DOI: 10.1016/s0735-1097(02)01926-5
|View full text |Cite
|
Sign up to set email alerts
|

differential effects of the angiotensin-converting enzyme inhibitor lisinopril versus the beta-adrenergic receptor blocker atenolol on hemodynamics and left ventricular contractile function in experimental mitral regurgitation

Abstract: Although lisinopril significantly reduced preload, its effect on LV contractility was insignificant in experimental MR. Conversely, atenolol, when added to lisinopril, achieved maximum hemodynamic benefit and also restored LV contractility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
1
7

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 25 publications
3
53
1
7
Order By: Relevance
“…However, in this model, there is no progressive change in the severity of the MR. These differences may relate to the severity of the initial insult: in previous studies initial induction of RF was ϳ60 -70% (25,26), whereas in our model initial RF was 50%.…”
Section: Discussioncontrasting
confidence: 52%
“…However, in this model, there is no progressive change in the severity of the MR. These differences may relate to the severity of the initial insult: in previous studies initial induction of RF was ϳ60 -70% (25,26), whereas in our model initial RF was 50%.…”
Section: Discussioncontrasting
confidence: 52%
“…In 1 study, 3-month treatment with atenolol reduced mitral regurgitant volume, improved LV end-systolic stiffness, and decreased left atrial and pulmonary artery pressures, but an angiotensin-converting enzyme inhibitor did not have these favorable effects. 19 ␤-Blockers improve the contractile function of cardiomyocytes isolated from dogs with severe mitral regurgitation by restoring contractile elements. 20 However, ␤-blockers had no favorable effect when pacing is added to increase heart rate, suggesting that slowing of heart rate is an important mechanism of benefit.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the benefits might be more pronounced if β-blockade was started early, before the development of irreversible LV dysfunction. Animal studies have shown that β-blockade could improve LV systolic function in chronic MR. [9][10][11] Recent clinical studies have also shown that β1-blockade may improve LV systolic function in chronic organic MR, but a beneficial effect on LV remodeling is uncertain. 12,13 There have been no studies yet demonstrating that β-blockade improves LV remodeling in chronic organic MR.…”
Section: Editorial See P 624 Clinical Perspective On P 762mentioning
confidence: 99%
“…23 Carabello et al 10 reported that β1-blockade restored impaired LV systolic function in a canine model of chronic organic MR with congestive heart failure. This beneficial There are no differences in LVEDV, LVESV, LV mass index, LVFS, and LVEF between the control and β-blockade groups at baseline and week 2 (all P values >0.05).…”
Section: β-Blockade In Chronic Organic Mrmentioning
confidence: 99%
See 1 more Smart Citation